Flipped Classroom Learning Process by Using Cloud Learning to Enhance Information Media and Technology Skills for Pre-Service Teachers - Hemarak, Monsiri; Aumgri, Charinthorn; Apirating, Kaiyasit (JOURNAL OF SOUTHERN TECHNOLOGY, 2023)
At present, the flipped classroom has become a new learning model for the 21st century in the age of globalization. Communication technology plays important roles in human livelihoods. Modern communication technology transforms learning models and lesson presentations from lectures to content reviews at home. The objectives of this research were 1) to develop a learning management system for the flipped classroom learning process by using cloud learning to enhance information media and technology skills for pre-service teachers, and 2) to compare learning achievement between pretest and posttest results of these pre-service teachers who were taught through the flipped classroom learning process by using cloud learning to enhance information media and technology skills. In this study, the population included 60 second-year teacher students in the physical education programme at Nakhon Pathom Rajabhat University in the first semester of the 2021 academic year. Simple random sampling was used to select 30 participants. The research instruments consisted of 1) lesson plans, 2) pretest and posttest, 3) cloud learning media, and 4) an assessment form on students’ satisfaction. Statistics for the data analysis were mean, standard deviation, and t-test. It was revealed that the development of the learning management for the flipped classroom learning process by using cloud learning consisted of 5 steps: topic selection, topic analysis, design of the learning management for the flipped classroom through cloud learning, testing and lesson revision. It was also found that the overall development of the learning management for the flipped classroom through cloud learning was at a high level ( = 4.47, S.D. = 0.57). The students’ learning achievement after the intervention was higher at statistical significance at the .05 level. The learning effectiveness (E1/E2) was 84.92/80.67. The participants’ satisfaction was at a very high level ( = 4.55, S.D. = 0.55). The findings of this study are helpful for teacher students in other disciplines who are not skillful in information media and technology for preparing themselves before their teaching internship in applying a classroom method for the 21st century. In addition, the results can be used as guidelines for developing learning management in flipped classroom learning process by using cloud learning to enhance information media and technology skills as well as for organizing creative learning activities for students in the teaching profession. The results can also be expanded in research studies in other teaching fields and the results are beneficial for the future.